Deploying Genome Editing Tools for Dissecting the Biology of Nut Trees - Walawage, Sriema L.; Zaini, Paulo A.; Mubarik, Muhammad S.; Martinelli, Federico; Balan, Bipin; Caruso, Tiziano; Leslie, Charles A.; Dandekar, Abhaya M. (Frontiers in Sustainable Food Systems, 2019)
Walnuts are among the most important nut crops grown in temperate regions of the world. Commercial production in California, and increasingly worldwide, relies on only few clonally grafted scion genotypes, particularly ‘Chandler’, and more recently clonally propagated disease-resistant rootstocks. Diseases, nematodes, insect pests, abiotic stresses, and other nutritional and environmental factors, can reduce walnut productivity and quality, affecting grower profitability. The California Walnut Breeding Program at UC Davis has developed and released scion cultivars and rootstocks to help address some of these problems. Recent sequencing of the walnut genome is expected to speed walnut breeding by facilitating development of molecular markers that can be linked to phenotypic traits, and by reducing the time needed to screen new genotypes, but conventional breeding of tree crops is still a long-term proposition. Here we describe a toolkit that uses a CRISPR-Cas9 system to enable rapid and precise editing of the genomes of currently grown commercial clonal walnut genotypes. A computational tool was developed to aid selection of guide RNAs targeting specific genomic sites and to identify potential off-target sites. As a proof-of-concept, the gene encoding phytoene desaturase (PDS) of walnut was targeted, disrupting its expression. This resulted in albino leaves; a dominant visual phenotype associated with the successful editing of this gene. This toolkit can now be adapted to other important tree crop members of the order Fagales, which includes other valuable nuts and trees species such as pecans, butternuts, chestnuts, hickory nuts, hazelnut, wingnut and oaks.